Alimentação e rede urbana na Amazônia brasileira: um estudo das transformações e permanências nos hábitos alimentares de idosas nas cidades de Tefé, Alvarães e Uarini, Amazonas. - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The Amazon is definitely an area of interest for the study of differences in access to food, and with the rapid process of modernization via communication networks and trade it impacts on dietary habits, especially in small and medium cities. The main objective of this thesis was to analyze the elderly population (female) of three cities of Amazonas State: Tefé, Alvarães and Uarini, related to the transformations and continuities in dietary habits. The hypothesis was that the format of the urban network and the relationship of rural production surrounding the cities are key elements to understand the geography of food in the Amazon. Another hypothesis is related to social development policies, which resulted in a monetization of economic dynamics, i.e., the universal retirement intensified the transition in dietary habits, hence the importance of analyzing how this transition occurs among the elderly, especially women who traditionally are responsible for cooking. To achieve the proposed objective the concepts of old age, urban network, and food and health geography were studied. A survey of secondary data on the elderly and the profile of the cities in the database IBGE, Datasus, UNDP were also analyzed. Therefore, the demographic quantitative census data contributed to understanding the dynamics of the processes and deepen the analysis that was built through the use of qualitative methods, i.e., techniques were used such as interviews, oral history aspects recorded with the permission of the interviewees. As for the interview instrument used, this was built from the systematization of open and semi-structured questions, which in turn led to a closer relationship with the world of the elderly evaluated. To analyze the changes and continuities in dietary habits, a formulary was applied. It was reshaped by the Center for Studies and Research of Cities in the Brazilian Amazon (NEPECAB) to meet the reality of the Amazon, in addition to showing the changes and continuities in eating habits with this form also whether they have found the economic, cultural changes and impacts of certain policies. In addition to insertion in the market economy, the populations of the three cities that make up the micro urban network of the Mid Solimões region, are also entering the “age of supermarkets", especially the breakfast, which is basically composed of bread and butter, coffee with sugar, and sometimes milk powder. This change is valid for the population as a whole and for the elderly. As for other meals, a difference has been noticed between the older and the rest of the population, where the majority of them choose, even during the overflowing rivers, fish, while the rest of the residents of these cities fail to consume the fish and opt for processed products.
Keywords: Rede Urbana; Geografia da Alimentação; Tefé; Alvarães; Uarini.; Amazonas; Idoso; Urban Network; Geography of Food; CIÊNCIAS HUMANAS: GEOGRAFIA